2016
DOI: 10.1152/ajplung.00322.2015
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myofibroblast differentiation by cardiac glycosides

Abstract: ] ratio may promote the expression of cyclooxygenase-2 (COX-2), a critical enzyme in the synthesis of prostaglandins. Given antifibrotic effects of prostaglandins through activation of protein kinase A (PKA), we examined if cardiac glycosides stimulate COX-2 expression in human lung fibroblasts and how they affect myofibroblast differentiation. Ouabain stimulated a profound COX-2 expression and a sustained PKA activation, which was blocked by COX-2 inhibitor or by COX-2 knockdown. Ouabain-induced COX-2 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…To our knowledge, there are no reports specifically demonstrating the ability of cardiac glycosides to prevent CAF differentiation. Interestingly, recently published data indicate an anti-fibrotic effect of ouabain through upregulation of COX-2 in lung fibroblasts, likely sharing a mechanism with our findings at the level of SMAD activity [55]. Given the abundance of published reports demonstrating that CAFs are able to facilitate the invasiveness of otherwise quiescent tumor cells, work toward the development of CAF-targeting therapeutic agents is warranted [8].…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge, there are no reports specifically demonstrating the ability of cardiac glycosides to prevent CAF differentiation. Interestingly, recently published data indicate an anti-fibrotic effect of ouabain through upregulation of COX-2 in lung fibroblasts, likely sharing a mechanism with our findings at the level of SMAD activity [55]. Given the abundance of published reports demonstrating that CAFs are able to facilitate the invasiveness of otherwise quiescent tumor cells, work toward the development of CAF-targeting therapeutic agents is warranted [8].…”
Section: Discussionsupporting
confidence: 67%
“…A number of important studies have shown the role of NKA inhibition and elevation of the [Na + ]i/[K + ]i ratio in the activation of Src-EGFR-MAPK- and Akt-mediated signaling pathways triggered by CTS, and readers are referred to a recent review which more thoroughly addresses this topic [ 83 ]. The importance of this concept is highlighted by recent data showing that NKA inhibition by CTS triggers TGFβ-induced fibrosis in cultured human lung fibroblasts via [Na + ]i/[K + ]i-mediated signaling which results in augmented expression of COX-2 [ 84 ] and downregulation of TGFβ2R [ 85 ]. Cumulatively, these studies have broadened the understanding of the role of CTS signaling through the NKA in human disease.…”
Section: Cts (Cardiotonic Steroids) Nka and Fibrosismentioning
confidence: 99%
“…Elevation of [Ca 2+ ] i , in turn, leads to its interaction with calmodulin and other Ca 2+ i sensors and activation of Ca 2+ response elements detected within promoters in hundreds of genes (for a comprehensive review, see [ 135 , 136 , 137 ]). Thus, for example, sharp elevation of cyclooxygenase 2 (COX-2) mRNA content seen in ouabain-treated human lung fibroblasts was completely abolished by Na + /Ca 2+ exchanger inhibitor KB-R4943 [ 138 ].…”
Section: Search For Intracellular Na + and K mentioning
confidence: 99%
“…Importantly, the action of ouabain was absent in p85-KO mice, thus suggesting that side-by-side with the positive inotropic effect, the treatment with Digitalis prevents pathological cardiac hypertrophy and heart failure through activation of PI3KIA [ 167 ]. Our recent study demonstrated that anti-fibrotic action of cardiac glycosides documented by the suppression of myofibroblast differentiation in TGF-β-treated human lung fibroblasts is mediated by dissipation of transmembrane gradients of monovalent cations [ 138 , 168 ]. To the best of our knowledge, the role of Na + ,K + -ATPase inhibition and the elevated [Na + ] i /K + ] i ratio in PI3K/Akt-mediated signaling triggered by CTS has not been explored yet.…”
Section: Search For Na + I K mentioning
confidence: 99%